2008
DOI: 10.1097/ccm.0b013e318174d89f
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma interleukin-6 in donors is associated with lower recipient hospital-free survival after cadaveric organ transplantation*

Abstract: Among brain-dead organ donors, older age donors contribute fewer organs for transplantation, and increased donor interleukin-6 level before organ procurement is associated with lower recipient six-month hospital-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 17 publications
5
72
0
4
Order By: Relevance
“…It is well-known that donor brain death results in a systemic inflammatory response (5) that can increase graft immunogenicity (6) and is associated with inferior posttransplant outcomes (7). However, there is presently a gap in knowledge regarding the specific cellular and molecular pathways responsible for the initiation of the deceased donor inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that donor brain death results in a systemic inflammatory response (5) that can increase graft immunogenicity (6) and is associated with inferior posttransplant outcomes (7). However, there is presently a gap in knowledge regarding the specific cellular and molecular pathways responsible for the initiation of the deceased donor inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the evaluation of non-invasive kidney injury biomarkers from perfusate solution could add a greater predictive value to kidney viability and allograft outcomes as concede assessment at multiple time points during preservation. Moers et al (47) have investigated for the first time six important perfusate biomarkers that have been supported in different studies and are already in use by various transplant centres (48)(49)(50)(51)(52). These biomarkers are; lactate dehydrogenase (LDH), aspartate aminotransferase (ASAT), total glutathione-S-transferase (GST), alanine-aminopeptidase (Ala-AP), N-acetyl-β-Dglucosaminidase (NAG), and heart type fatty acid binding protein (H-FABP).…”
Section: Perfusate Biomarkersmentioning
confidence: 99%
“…[15,203] Murugan and colleagues demonstrated an inverse relationship between donor plasma IL-6 levels and recipient six-month hospital free survival. [172] Kaneda et al also showed that higher donor IL-6 levels increased the risk of recipient death within 30 days of lung transplant. [205] T H 17 cells, through production of IL-17, stimulate inflammation in donor organs.…”
Section: Type 17 Associated Cytokinesmentioning
confidence: 99%
“…[163] Interestingly, this group also analysed serum cytokine levels in human BD donors and showed that they were not significantly elevated. [ [129,172,196] Additionally, IL-10 has been shown to be upregulated in human livers [15] and kidneys. [197] Work undertaken by Li et al suggested that IL-10 expression after BD may be important in stimulating apoptosis of graft infiltrating lymphocytes through activation of the Fas/Fas Ligand pathway.…”
Section: Type 1 Associated Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation